Penerapan Inquiry Learning Berbasis Merdeka Belajar untuk Meningkatkan Hasil Belajar Fisika Siswa Kelas X - Rezeki, Nani Sri; Damanik, Dede Parsaoran; Purba, Andre Agachi (Mahesa Research Center, 2025)
Physics learning practices in schools are still largely dominated by monotonous, teacher-centered approaches, which contribute to low student engagement and academic achievement. This study aims to improve student activeness and Physics learning outcomes through the implementation of the Inquiry Learning model based on the Merdeka Belajar (Freedom to Learn) concept. The research employed a Classroom Action Research (CAR) design conducted in two cycles. The subjects of this study were 25 tenth-grade students at SMA Desa Maju. Instruments used included multiple-choice tests to measure learning outcomes and observation sheets to assess student engagement. The results indicated a significant improvement, with the average learning score increasing from 29.00 in the pre-cycle to 47.50 in the first cycle, and reaching 87.83 in the second cycle. Student engagement also improved progressively in each session. These findings demonstrate that the implementation of the Inquiry Learning model based on the Merdeka Belajar concept is effective in enhancing both engagement and Physics learning outcomes.